Disparitas Pemahaman Hakim dalam Penyelesaian Sengketa Konsumen (Kajian Putusan No. 350 K/Pdt.Sus-BPSK/2016 dan NO.10/Pdt.Sus-BPSK/2016/PN.Plk) - Bachri, Rifkiyati; Kurniawan, Yunan Prasetyo (Khairun Law Journal, 2018)
Judge decision NO. 350 K/Pdt.Sus-BPSK/2016 and Judge decision NO.10/Pdt.Sus-BPSK/2016/PN.Plk are 2 (two) of the 127 (one hundred and twenty seven) verdicts of BPSK annulled by the Supreme Court (MA) on October 27, 2017. Where MA argued the two verdicts were not the authority of BPSK. Thus, problems arise whether the decision NO. 350 K/Pdt.Sus-BPSK/2016 and the decision NO.10/Pdt.Sus-BPSK/2016/PN.Plk are the competence of BPSK in resolving consumer disputes or not. To answer these problems, normative legal research methods are used, so that the conclusion is that the verdict NO.10/Pdt.Sus-BPSK/2016/PN.Plk is not the Palangkaraya BPSK competency in deciding because Sancho is not the final consumer protected by UUPK, so if the Supreme Court annulled the decision of the Palangkaraya BPSK is true. Meanwhile, verdict NO. 350 K/Pdt.Sus-BPSK/2016 is true Coal BPSK competency to decide consumer disputes because Dermasnyah Pane is the final consumer protected by UUPK, so if the Supreme Court annulled the decision of Coal BPSK is not true.